GAMBARAN EFEK SAMPING KONTRASEPSI KB SUNTIK 1 BULAN PADA AKSEPTOR KB SUNTIK 1 BULAN DI RUMAH BERSALIN DAN BALAI PENGOBATAN UMMI PALEMBANG - Ratna Dewi; Angges (Jurnal Kesehatan dan Pembangunan, 2023)
Injectable KB is a contraceptive that injects a synthesized progestin that has an effect like the original progesterone from a woman's body. The aim is to find out the description of the side effects of 1 month injectable birth control contraception on 1 month injectable family planning acceptors. This type of research is descriptive with cross sectional design. The research subjects were all mothers who received 1 month injection of Rumah bersalin dan balai pengobatann ummi Palembang, as many as 26 respondents. The results showed that 26 respondents who received 1 month injection of family planning who had a 28-day menstrual cycle, namely 24 respondents (92.3% and who had a 35-day menstrual cycle, namely 2 respondents (2%). Complaints of acceptors of 1 month injection of family planning in the form of headaches 5 respondents (19.2%), menstrual disorders 2 respondents (7.7%, vaginal discharge 19 respondents (0.0%) and no complaints 19 respondents (73.0%) Changes in body weight of injectable birth control acceptors 1 month which increased, namely 18 respondents (69.2% and which did not increase, namely 8 respondents (30.8%). It is hoped that the leadership and midwives of Rumah bersalin dan balai pengobatann ummi Palembang, center can provide information or counseling to mothers about the side effects of 1st injection birth control months and types of contraception so that patients can determine the appropriate choice of contraception.